(untitled) (Indian Journal of Animal Production and Management, 2017)
Vocalization in dairy animals is thought to be one of the best means of conversation between each other as well as with environment. The present investigation was carried out on 12 lactating crossbred Karan Fries cows. The vocal signals from these animals were recorded for sufficient time in order to receive 50 complete sound clips. The various acoustic features were extracted in order to establish the relationship between these and various body related measurements. The yielding capacity of KF crossbred cows was found to be significantly affected by only their heart girth (P< 0.05) and length of bridge of nose (P< 0.01). Moreover, among various acoustic features of vocalizations investigated in present study only total energy, call duration, F5 and mean formant dispersion reflected a significant (P< 0.05) effect on yielding capacity of KF crossbred cows. Among various body measurements only the heart girth reflected significantly (P< 0.01) medium correlation with total energy of vocalizations of KF cows, but it was an inverse correlation (-0.296), indicating that the total energy of the cow vocalization will decrease with an increase in its heart girth. Therefore, in present study the heart girth of high yielding cows was observed to be significantly higher than low yielding cows and total energy of vocalizations of high yielding cows was observed to be less than low yielding cows.